Environmental Journalism in the Environmental Conflict: A Case Study of Mainstream and Alternative Media Discourse on the Conflict of Cement Factory Construction in Rembang, Indonesia - Khumaid Akhyat Sulkhan (Asian Journal of Media and Communication, 2022)
This paper aims to reveal the discourse produced by mainstream and alternative media about the conflict of the cement factory construction of PT Semen Indonesia in Rembang, Central Java, Indonesia. This study has applied critical discourse methods proposed by Norman Fairclough, focusing on three discourse levels: texts, discursive practices, and socio-cultural practices. The analyses were conducted on the selected texts from June 2014 to December 2015 in Liputan6.com as the mainstream media category and Selamatkanbumi.com as the example of alternative media. This study found that Liputan6.com lacks environmental and biocentric values. It tends to support the discourse of ‘mining for welfare’. Liputan6.com has marginalized the arguments of the factory repellent by contrasting them with the experts’ and politicians’ statements without in-depth investigations on the impact of cement factory construction on the local environment. The news tends to be a one-sided reportage. Meanwhile, Selamatkanbumi.com quite aggressively publishes news about this conflict, framed with the discourse of ‘mining destroys the environment’. Selamatkanbumi.com has shown its alignment with the environmental crisis and has practiced the principal attitudes of environmental journalism, except professionalism. They were lack of professionalism since they often just published press releases or opinions that met with their interest, not processes with proper journalistic works.